2018
DOI: 10.1021/acs.langmuir.8b02789
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Point Pressures of Hydrocarbon Mixtures in Multiscale Volumes from Density Functional Theory

Abstract: Accurate characterization of the bubble point pressure of hydrocarbon mixtures under nanoconfinement is crucial to the prediction of ultimate oil recovery and well productivity of shale/tight oil reservoirs. Unlike conventional reservoirs, shale has an extensive network of tiny pores in the range of a few nanometers. In nanopores, the properties of hydrocarbon fluids deviate from those in bulk because of significant surface adsorption. Many previous theoretical works use a conventional equation of state model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Hysteresis disappears at a lower temperature for smaller nanopores. For the record, a similar hysteretic phenomenon of confined mixture has also been found in several works recently. As the main purpose of this work, the location of the hysteresis end point for a specific system will be carefully estimated next.…”
Section: Resultssupporting
confidence: 61%
“…Hysteresis disappears at a lower temperature for smaller nanopores. For the record, a similar hysteretic phenomenon of confined mixture has also been found in several works recently. As the main purpose of this work, the location of the hysteresis end point for a specific system will be carefully estimated next.…”
Section: Resultssupporting
confidence: 61%
“…Previous studies have demonstrated that the pore size and LJ size diameter are the key parameters to determine the shift of critical temperature. ,, Furthermore, the linear relationship in a log–log scale is found to be useful to describe the relationship between the dimensionless shift of critical temperature, Δ T , and the normalized pore dimension, m , which is the ratio of the pore radius to the LJ size parameter. , Meanwhile, MD simulations have shown the difference between Δ T in cylindrical nanopores and that in slit nanopores with the same pore dimension . Therefore, the Δ T as a function of normalized pore dimension, m , in cylindrical nanopores and slit nanopores can be separately expressed as where a 1 and b 1 are the fitting parameters for cylindrical nanopores while a 2 and b 2 are the fitting parameters for slit nanopores.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Previous studies have demonstrated that the pore size and LJ size diameter are the key parameters to determine the shift of critical temperature. 6,7,29 Furthermore, the linear relationship in a log−log scale is found to be useful to describe the relationship between the dimensionless shift of critical temperature, ΔT, and the normalized pore dimension, m, which is the ratio of the pore radius to the LJ size parameter. 7,29 Meanwhile, MD simulations have shown the difference between ΔT in cylindrical nanopores and that in slit nanopores with the same pore dimension.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further opportunity remains to design micro and nano-models that can capture molecular-scale information. This may include the development of nanofluidics devices [253][254][255] , which have proven to be excellent tools for accessing critical phenomena at the molecular level, including non-conventional phase behaviors. However, challenges still need to be addressed in term of experimentation (clogging, nonvalidity of conventional fluid mechanics equations, etc.).…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%